2021
DOI: 10.1021/acs.chemmater.0c03610
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Induced Deprotonation of Thiol Ligands Impacts the Optical Response of CdS Quantum Dots

Abstract: Cadmium chalcogenide quantum dots (QDs) passivated by thiol-based ligands exhibit several advantages in their applications in lighting, sensing, and imaging technologies. However, their emission is sensitive to thiol concentrations, pH conditions, and temperatures. Using calculations based on the density functional theory, we identify conditions for thiol/thiolate equilibrium at the CdS QD surface that either eliminate or introduce optically inactive hole trap states favoring or disfavoring the emission. Our c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 57 publications
1
33
0
Order By: Relevance
“…Such computational methodology has been extensively tested and used across a broad variety of previous modeling studies. 31,35,36,47,69,70 Hirshfeld 61 charge analysis, as applied in Multiwfn 71 v3.7 software package, was used to obtain the charge distribution on all the atoms and calculate the Inverse Participation Ratios (IPRs). We obtained the partial density of states (PDOS) plots from Gaussian outputs using GaussSum software package 72 and visualized atomic structures and orbitals using the VESTA 73 v3.5.7 software.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such computational methodology has been extensively tested and used across a broad variety of previous modeling studies. 31,35,36,47,69,70 Hirshfeld 61 charge analysis, as applied in Multiwfn 71 v3.7 software package, was used to obtain the charge distribution on all the atoms and calculate the Inverse Participation Ratios (IPRs). We obtained the partial density of states (PDOS) plots from Gaussian outputs using GaussSum software package 72 and visualized atomic structures and orbitals using the VESTA 73 v3.5.7 software.…”
Section: Methodsmentioning
confidence: 99%
“…Several simulation techniques, ranging from the adiabatic ground state to non-adiabatic excited-state calculations, have been applied to understand the photo-chemo-physical properties of QDs in detail. 25–28 However, most of these attempts 29–37 have focused on stoichiometric QDs (with an equal number of cation and anion atoms) that are less frequently obtained from the conventional synthesis. The more common non-stoichiometric QDs, with cation-to-anion ratios deviating from one, that are critical to many optical and photocatalytic applications, remain largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of the fluorescence response of CdZnSeS-pATP QDs to acidity is inferred as follows. It is reported that the low fluorescence intensity under acidic conditions results from the dissociation of the thiol ligand on QDs due to protonation of the surface-binding thiolate [ 43 , 44 , 45 ]. As the thiol ligand, pATP (pK a = 6.86) [ 46 ] can also dissociate from CdZnSeS QDs, which causes the direct exposure of CdZnSeS QD surfaces to solvent molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, molecular simulations have proven to be a reliable approach to investigate the atomic and electronic structure of colloidal QDs. Atomistic modelling methods were used for the characterization of the ground state [22][23][24][25] as well as excited states [26][27][28][29][30][31][32][33][34][35][36] of CdSe QDs. Those theoretical studies investigated the origin of defect emission of colloidal QDs and provide a better understanding of QDs photophysics, giving guidance to the experimental design of novel materials, e.g., by the passivation method.…”
Section: Introductionmentioning
confidence: 99%